CLINICAL CHARACTERISTICS OF ACUTE RESPIRATORY DISEASE IN INFANTS IN ALMATY, KAZAKHSTAN - R. S. Idrisova; Z. R. Eshibekova; L. R. Idrissova; A. A. Bisebaeva (LLC "Diagnostics and Vaccines", 2017)
Acute respiratory infections and diarrheas are the main cause of hospitalization. We do not have a routine practice of etiological verification of respiratory viruses, the diagnosis is based on clinical presentation and instrumental investigations. We do not perform identification of respiratory syntycial virus (RSV), however there are effective methods of specific prophylactic and treatment with monoclonal antibodies available worldwide. Another point is wide application of antibiotics without clear indications on bacterial infection, especially if a patient is hospitalized. We analyzed clinical data of children aged 0-3 months with acute respiratory viral infections and found a big number of patients with bronchoobstruction associated with bronchiolitits which in fact points on possible involvement of RSV.